Immunoexpression of interferon-gamma in the interdental gingiva of chronic periodontitis patients with interferon-gamma (+874A/T) rs62559044 polymorphism - Nadia Sheibak; Zahra Heidari; Hamidreza Mahmoudzadeh-Sagheb (Elsevier, 2022)
Interferon-gamma (IFNγ), which is involved in inflammation, has an essential role in the pathogenesis of chronic periodontitis (CP). The association of IFNγ +874A/T gene polymorphisms with a higher incidence of CP has been reported previously. We investigated the immunoexpression of IFNγ in human gingiva from CP patients with IFNγ +874A/T gene polymorphisms compared to a healthy group. Biopsies from interdental gingiva (n = 60) were obtained from CP patients (n = 38) and individuals who had clinically healthy gingiva (n = 22). The specimens were classified according to genotypes of IFNγ +874A/T gene polymorphism using amplification-refractory mutation system-polymerase chain reaction (ARMS-PCR) (10AA, 18AT, and 10 TT). After tissue processing and slide preparation, we evaluated the expression levels of IFNγ in the interdental gingiva using the immunohistochemistry technique. Values were compared between two study groups by Mann-Whitney and Kruskal-Wallis analysis. P < 0.05 was considered the level of significance. There was a noticeable increase in the immunoexpression of IFNγ in the gingival epithelium, fibroblasts, and capillaries of gingival tissue from CP patients compared to the control group. We found different levels of IFNγ expression in different parts of the gingival epithelium. The highest levels were found in the middle regions of the gingival epithelium in patients with TT genotypes. Immune cells and vascular endothelium of gingiva in the AA group also showed increased expression of IFNγ. Results suggest that IFNγ +874A/T gene polymorphism may change the expression level of IFNγ and subsequently the progression of CP.